THE DIFFICULTIES OF SPEAKING SKILL ON THE LEARNING OF ENGLISH FOR LEARNERS AND SOLUTION TO THE PROBLEMS (Proceedings of International Educators Conference, 2023)
English as an global language is used and realized through human beings no longer only from English speakme international locations but additionally from non-English talking countries. In this research, the researcher makes use of some techniques and references that carefully reviewed to accumulate records associated to the data required for finishing this article. It is discovered that Basic English newcomers typically face countless barriers in getting to know English, such as the difficulties as nicely as Teaching English language through role-play is very influential in that it enhances students‟ publicity to language which is regarded as the key aspect to pace up the language getting to know process. Students by way of producing speech in role-play activities can have a exact command of communicative competence. Moreover, behavior of role-play activities can furnish a stress free gaining knowledge of surroundings the place students revel in using the language. Role-play activities will enable students to obtain self-confidence and consequently they will stand a higher risk of advertising their speakme skills.